Sustainability gap of public debt: importance of interest rates and a new decomposition with premia - Elmar Dönnebrink; Nils Grevenbrock (Empirica, 2022)
Sustainability gaps ( S2 indicators) are frequently used in national and international reports to assess the sustainability of public finances. For instance, in the European Commission's Debt Sustainability Monitor (DSM) the indicators are analyzed in comparisons across (policy) scenarios, countries and time. The report's findings play a crucial role in the context of the Stability and Growth Pact and the European Semester. As a result, sustainability gaps have a significant indirect influence on policy decisions. In this paper, we analyze two non-transparent properties of these indicators. First, the response of these indicators to changes in the interest rate-growth (r-g) differential is not readily predictable in terms of both strength and direction. Second , in our examples for low values of r-g (in a range of 0.5%), highly uncertain projections for distant periods after 2070 explain about 80% of the indicators' values. To address these problems, we develop a new decomposition that takes into account the notion of premia (Reis 2021) and hence allows for a more transparent discussion of the sustainability of public debt.
Keywords: H6; E43; D52; J11; 330; Public debt; Interest rates; Fiscal sustainability; Public budget